Answer:
(x +3)^2 +(y -4)^2 = 52
Explanation:
The standard form equation of a circle with center (h, k) and radius r is ...
(x -h)^2 +(y -k)^2 = r^2
We are given the value of (h, k), and we can find the value of r^2. Using the values of h and k, our equation is ...
(x +3)^2 +(y -4)^2 = r^2
Since we know this equation is satisfied by the point (1, -2), we can use this point in the equation to find r^2:
(1 +3)^2 +(-2 -4)^2 = r^2
16 +36 = r^2 = 52
The equation of the circle is ...
(x +3)^2 +(y -4)^2 = 52